Irrigation and Nitrogen Regimes Promote the Use of Soil Water and Nitrate Nitrogen from Deep Soil Layers by Regulating Root Growth in Wheat - Liu, Weixing; Ma, Geng; Wang, Chenyang; Wang, Jiarui; Lu, Hongfang; Li, Shasha; Feng, Wei; Xie, Yingxin; Ma, Dongyun; Kang, Guozhang (Frontiers in Plant Science, 2018)
Unreasonably high irrigation levels and excessive nitrogen (N) supplementation are common occurrences in the North China Plain that affect winter wheat production. Therefore, a 6-yr-long stationary field experiment was conducted to investigate the effects of irrigation and N regimes on root development and their relationship with soil water and N use in different soil layers. Compared to the non-irrigated treatment (W0), a single irrigation at jointing (W1) significantly increased yield by 3.6-45.6%. With increases in water (W2, a second irrigation at flowering), grain yield was significantly improved by 14.1-45.3% compared to the W1 treatments during the drier growing seasons (2010-2011, 2012-2013, and 2015-2016). However, under sufficient pre-sowing soil moisture conditions, grain yield was not increased, and water use efficiency (WUE) decreased significantly in the W2 treatments during normal precipitation seasons (2011-2012, 2013-2014, and 2014-2015). Irrigating the soil twice inhibited root growth into the deeper soil depth profiles and thus weakened the utilization of soil water and NO3-N from the deep soil layers. N applications increased yield by 19.1-64.5%, with a corresponding increase in WUE of 66.9-83.9% compared to the no-N treatment (N0). However, there was no further increase in grain yield and the WUE response when N rates exceeded 240 kg N ha-1 and 180 kg N ha-1, respectively. A N application rate of 240 kg ha-1 facilitated root growth in the deep soil layers, which was conducive to utilization of soil water and NO3-N and also in reducing the residual NO3-N. Correlation analysis indicated that the grain yield was significantly positively correlated with soil water storage (SWS) and nitrate nitrogen accumulation (SNA) prior to sowing. Therefore, N rates of 180-240 kg ha-1 with two irrigations can reduce the risk of yield loss that occurs due to reduced precipitation during the wheat growing seasons, while under better soil moisture conditions, a single irrigation at jointing was effective and more economical.